ECTANISATION OF LOIS LOWRYâ€™S THE GIVER NOVEL INTO PHILIP NOYCEâ€™S THE GIVER MOVIE - Sitti Maryam MY Mahmud (JURNAL VENUS, 2018)
This research was about Ecranisation which aimed to find out the kinds of changes in the ecranisation process and and the motive of ecranisation process of novel into movie â€œThe Giverâ€. This research focused on Enesteâ€™s Theory about Ecranisation. The data were analyzed through descriptive qualitative method. This research used note taking as the instrument to get the valid data. The findings revealed that ecranisation process were only found in characters and settings element between novel and movie and the motive of ecranisation process to make the story is interesting of perfect for audiences. The researcher concluded that the book and the movie are two different products which were never be the same.